Enhancing the role of the libraries in South African Higher Education Institutions through Research Data Management: A case study of Cape Peninsula University of Technology - Ntja, Bulelwa (Library and Information Studies Centre (LISC), 2023)
Research Data Management (RDM) is one of the top trends in academic libraries. Academic libraries are faced with the challenge of implementing RDM services. Libraries that are not yet offering support for research data may be at the stage of developing RDM services. The main objective of this study was to identify the experiences of one institution, the Cape Peninsula University of Technology (CPUT), in the introduction and implementation of RDM services with the intention of informing other SA HEIs about their offerings and experiences. The Digital Curation Centre (DCC) Lifecycle Model was used to guide the investigation in this study. The model helped to achieve the study's sub-objectives, which were: to establish to what extent RDM services have been adopted at CPUT, to identify experiences of librarians, and to make recommendations for successful implementation of RDM services. This is a qualitative case study in which data were collected through document analysis and interviews. The study found that CPUT Libraries offer data management planning assistance, storage and management of data, and guidance and training in support of RDM. The experiences of CPUT in the introduction and implementation of RDM that the study highlighted are the crucial role played by library management, the development of staff skills, the challenge of librarian workloads and attitudes, and researcher reluctance to engage with RDM and institutional partnerships. The study recommends among other things: piloting of the RDM project; continuous advocacy for RDM; reaching out to the research community for needs assessments and to provide necessary RDM training; implementation of RDM policy; and institutional, national and international partnerships.